Efektivitas Pemakaian Aplikasi Katakana Memory Hint Dalam Mata Kuliah Shokyuu Moji Goi Zenhan - Rita Arni (KIRYOKU, 2021)
This research is about the effectiveness of an Android application called the Katakana Memory Hint in learning Japanese letters during the Shokyuu Moji Goi Zenhan course. The course is taken by first-year students of the Japanese Language Education Study Program of Universitas Negeri Padang. This research focuses on one of the Japanese characters, the Katakana letters, because they are difficult to understand. For basic level learners, of course, they need media to help make it easier to learn the Katakana letters. Due to the rapid development of today's smartphone technology, Android applications have become a medium to help the learning process especially Japanese. This research is done to find out the advantages of an Android application called the Katakana Memory Hint designed by the Japan Foundation. This research applied the experimental method. The respondents were first-year students of the Japanese Language Education Study Program of Universitas Negeri Padang with the number of research sample of 30 people. The research findings show that the application is, as a matter of fact, effective in helping students to read and write the Katakana letters.